The Artist's Advantage: Better Integration of Object Information across Eye Movements. (September 2013) - Perdreau, Florian; Cavanagh, Patrick
Over their careers, figurative artists spend thousands of hours analyzing objects and scene layout. We examined what impact this extensive training has on the ability to encode complex scenes, comparing participants with a wide range of training and drawing skills on a possible versus impossible objects task. We used a gaze-contingent display to control the amount of information the participants could sample on each fixation either from central or peripheral visual field. Test objects were displayed and participants reported, as quickly as possible, whether the object was structurally possible or not. Our results show that when viewing the image through a small central window, performance improved with the years of training, and to a lesser extent with the level of skill. This suggests that the extensive training itself confers an advantage for integrating object structure into more robust object descriptions.